ACTUALIZATION OF REASONING PHILOSOPHICAL STANDARS IN PERSONAL DATA PROTECTION - FIRMAN MUHAMMAD ARIF (Pascasarjana IAIN Ambon, 2022)
The penetration of technology and information in personal data has been packaged with juridical regulations but has experienced a shift which results in legal inequality, abuse, stigma and criminalization. The reality of advances in information technology ensures that the person is a thief of personal data under the guise of a profession. The existence of personal data is analogous to humans personally who discuss the need for personal data protection. The absence of consensus on the classification of personal data and data protection enlivens the free trade that has the potential to be misused. The utilization of Islamic law methodology as an instrument is assessed to be up to date by elaborating various legal sources in it, such as maslahah mursalah and sadd al zari'ah. The problem of mursalah is realized by government policies that are repressive and advocacy. As for sadd al zari'ah as a preventive effort that silences and closes gaps that have the potential to cause digital crime. Various fiqh principles in politics and siyasa also provide a complete analysis of the substance. The existence of both requires the unification of certainty, justice and legal benefits to be combined. The existence of personal data in the modern world needs to be legitimized and confirmed in the form of regulation and the rule of law. The involvement of the government and stakeholders is absolutely necessary for the design of regulations that are not only administrative in nature but also provide criminal or civil sanctions. The rule of law before or after the formalization of specific regulations regarding the protection of personal data is ensured to guarantee security and comfort.